Survei Hubungan Asosiasi antara Pria dan Wanita dengan Mengonsumsi Rokok atau Vape - Nazwa Aulia A; Asti Lailatus S; Rayhan Akbar; Daffa R Nugraha; Cita Nafisah P (Pusat Riset dan Inovasi Nasional, 2023)
Smoking is a behavior that is easy to see around us. Currently, cigarettes are not only consumed by parents because many teenagers also consume them. In the research we conducted, it was proven that gender does not influence the use of cigarettes and vape. , variables such as where they live and their relationships are one of the reasons they consume cigarettes or vape. The impact that smoking can have is that it can increase the risk of various diseases, including heart disease, lung cancer, impotence, etc. This research aims to look at the association between men and women and consuming cigarettes or vape. The type of research carried out uses quantitative methods. The results of the study show that there is no evidence to suggest that there is an association between men & women and consuming cigarettes or vaping.